Exploring Promising Research Frontiers Based on Knowledge Maps in the Solar Cell Technology Field - Inchae Park (Sustainability, 2015)
Given the challenging environmental issues in the energy sector, the importance of strategic research and development (R&D) planning has been emphasized to manage a turbulent business situation. This study aims to propose a methodology for exploring promising research frontiers in the energy sector. To this end, first, core documents are collected from scientific documents such as patents and academic papers. Second, the research frontiers are extracted by clustering the core documents based on the bibliographic relations. Third, a knowledge map is generated by mapping the relations between research frontiers. Finally, the promising research frontiers (RFs) are identified by conducting dynamic analyses and the contents of promising RFs are suggested. As an illustration of the method, the field of solar cell technology is chosen and analyzed As a result, the promising research frontiers from the patent knowledge map are related to development (D) themes and promising research frontiers from scientific paper knowledge map are related to the research (R) themes. The proposed method and results can be utilized by researchers, R&D policy makers, and administrations in practice.